2009
DOI: 10.1590/s0001-37652009000300009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FGF-2 and EGF removal on the differentiationof mouse neural precursor cells

Abstract: Cell therapy for neurological disorders has advanced, and neural precursor cells (NPC) may become the ideal candidates for neural transplantation in a wide range of diseases. However, additional work has to be done to determine either the ideal culture environment for NPC expansion in vitro, without altering their plasticity, or the FGF-2 and EGF mechanisms of cell signaling in neurospheres growth, survival and differentiation. In this work we evaluated mouse neurospheres cultured with and without FGF-2 and EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 27 publications
(18 reference statements)
0
20
0
Order By: Relevance
“…Neural differentiation of placental stem cells with RA plus hBDNF resulted in 5-20 % of oligodendrocytic cells (Portmann-Lanz et al 2010). It has been reported that bFGF increased the proliferative potential of MSCs (Schwindt et al 2009;Sotiropoulou et al 2006). We suggest that the increased cell density with FGF and EGF can lead to cells with a higher positive CNPase level.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Neural differentiation of placental stem cells with RA plus hBDNF resulted in 5-20 % of oligodendrocytic cells (Portmann-Lanz et al 2010). It has been reported that bFGF increased the proliferative potential of MSCs (Schwindt et al 2009;Sotiropoulou et al 2006). We suggest that the increased cell density with FGF and EGF can lead to cells with a higher positive CNPase level.…”
Section: Discussionmentioning
confidence: 65%
“…The results from this study showed that the proportion of GFAP-positive cells in untreated cells was less than induced cells in DF/Ds/Fg/E group. GFAP can also be expressed by immature neural progenitor cells (Schwindt et al 2009). Long-term (14 days) exposure to RA dramatically reduced the GFAP-positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…These cellular structures represent three dimensional heterogeneous cell clusters, comprising stem cells, committed progenitors, as well as differentiated neural cells [7][8][9] . As growth factors maintain the proliferative characteristics of NS, their withdrawal will stop the proliferating process and will start the differentiation of cells [10] , leading to an increase in markers of fully differentiated neural cell populations, such as neurons and glial cells [7,11] . With the advances in stem cell biology, a debate has emerged regarding the origin of tumors, particularly gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…FGF-2 has been found to be a potent modulator of proliferation in culture of neonatal and adult precursor cells, supporting strong role of this factor in neurogenesis (Ford-Perriss et al 2001). Yet, FGF-2 mechanisms of cell signaling in neurospheres growth are still unclear (Schwindt et al 2009). It has been demonstrated that FGF-2 increases neural stem cell proliferation by upregulating of a VEGF receptor expression via stimulating phosphorylation of extracellular-regulated kinases Xiao et al 2007).…”
Section: Introductionmentioning
confidence: 99%